2012
DOI: 10.1021/jp302468x
|View full text |Cite
|
Sign up to set email alerts
|

UV Spectroscopy of DNA Duplex and Quadruplex Structures in the Gas Phase

Abstract: UV absorption spectroscopy is one of the most widely used methods to monitor nucleic acid folding in solution, but the absorption readout is the weighted average contribution of all species present in solution. Mass spectrometry, on the other hand, is able to separate constituents of the solution based on their mass, but methods to probe the structure of each constituent are needed. Here, we explored whether gas-phase UV spectroscopy can give an indication of DNA folding in ions isolated by electrospray mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 77 publications
(135 reference statements)
0
42
0
Order By: Relevance
“…have used IR spectroscopy to characterize the gas‐phase G4 structure . In a later work they have shown that also by means of UV spectroscopy G4 structures can be assessed in the gas‐phase . For investigating VUV photoabsorption in a gas‐phase G4, we have chosen the simplified dTGGGGT sequence which can form a tetramolecular G4 in the presence of NH 4 + counterions.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…have used IR spectroscopy to characterize the gas‐phase G4 structure . In a later work they have shown that also by means of UV spectroscopy G4 structures can be assessed in the gas‐phase . For investigating VUV photoabsorption in a gas‐phase G4, we have chosen the simplified dTGGGGT sequence which can form a tetramolecular G4 in the presence of NH 4 + counterions.…”
Section: Resultsmentioning
confidence: 69%
“…[31] In al ater work they have shown that also by means of UV spectroscopy G4 structures can be assessed in the gas-phase. [32] For investigating VUV photoabsorption in a gas-phase G4, we have chosen the simplified dTGGGGTs equencew hich can form at etramolecular G4 in the presenceo f NH 4 + counterions. Figure 5(a) displaysaphotofragmentation spectrum obtained after absorption of one 21 eV photon by the single (dTGGGGTÀ2H) 2À strand.S imilar to the case of (dTTAGGGÀ3H) 3À (Figure1a), extensive fragmentation is observed, in competition with ND1E into (MÀ2H) À .F igure 5(b,c) show the resultsf or photoionization of the correspondingG 4, that is, [(dTGGGGT) 4 + 3NH 4 À8H] 5À (b) and[ (dTGGGGT) 4 + 3NH 4 À7H] 4À (c).…”
Section: Resultsmentioning
confidence: 99%
“…We chose the parallel-stranded [dTGGGGT] 4 G-quadruplex DNA structure ( Fig. 1) because (1) starting atomic coordinates of [dTGGGGT] 4 are available from X-ray crystallography, [11][12][13][14] (2) the same molecular assembly was studied by nuclear magnetic resonance (NMR) as well and presents the same G-quadruplex core arrangement, although the thymine placement differs, with evidence for T-T interactions, [15][16][17] and (3) the central guanine-rich core remains very rigid in the gas phase, [18][19][20][21] thanks to the preservation of the G-quartet hydrogen bonds and to the coordination of three ammonium cations in-between the four guanine G-quartets. Only the position of thymines in the gas phase is less certain.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with the large amount of information available on their ground‐state properties, despite recent advances,22, 25, 3134 the nature of the excited electronic states of G‐Quads remains elusive.…”
Section: Introductionmentioning
confidence: 99%